The analysis of selected morphotic parameters of blood as potential diagnostics factors in pulmonary embolisms - Piech, Piotr; Obierzyński, Paweł; Staśkiewicz, Grzegorz; Kozioł, Maciej; Kozioł, Jadwiga; Opaliński, Hubert; Kuroska, Gabriela; Pieniążek, Patryk; Łuczyk, Robert Jan (Journal of Education, Health and Sport, 2017)
Introduction. Pulmonary embolism is a disease caused by stenosis or total obstruction of pulmonary trunk or its branches. Diagnostics of pulmonary embolism, despite development of laboratory and radiological tests, is still challenging. Such problem is particularly visible in surgical departments. The variety of symptoms, lack of parameters which could confirm diagnosis and limited access to angio-CT in some hospitals, make pulmonary embolisms a dangerous, life-threatening and easy to overlook disease. Aim of the study. The analysis of laboratory tests of hospitalized patient was conducted to find a blood parameter which would correlate with diagnosis made during angio-CT. Materials and methods. Laboratory and radiological tests results of 92 patients with pulmonary embolism suspicion were considered in this retrospective study. All of the patients were hospitalized in the Department of Orthopedics and Traumatology in SPSK4 in Lublin. Considered parameters were APTT, INR, MPV, PCT, PDE, HCT, MCV, MCH, MCHC, RBC, HGB, RDW, HDW. In the statistical analysis, Wilcoxon and Mann-Whitney tests were used. As significant were considered results with p<0,05. Results. Among all 92 patients with suspicion of pulmonary embolism, 57 (62%) had negative angio-CT results, while 35 (38%) were diagnosed with embolism. Statistical analysis showed correlation between some of the parameters: one concerning platelets (PCT – p=0,012), three concerning red blood cells (MCHC – p=0,033; RDW – p=0,002; HDW – p=0,001). Also, a strong correlation with INR was proven. Conclusions. Results of the study show, that there is a correlation between some of tested parameters and a suspicion of pulmonary embolism in angio-CT. Possibly, finding new correlations is a matter of further analysis and a bigger study group.